PERAN PENYULUH PERTANIAN DALAM PENGENDALIAN HAMA TIKUS PADA USAHA TANAMAN PADI (ORYZA SATIVA L.) DI DESA TOMPONG PATU - Yasinta Sao, Fransiska; Iawan Saputera Wanda, Taras; Noni, Sarlina (Universitas Cokroaminoto Palopo, 2025)
Agricultural extension workers have an important role in supporting agricultural development, with the main task of conveying information and providing technical guidance to farmers. Agricultural extension workers not only solve technical problems for farmers, but also function to support the social welfare of the community. This study aims to analyze the role of agricultural extension workers in controlling rat pests in rice farming in Tompong Patu Village, Kahu District, Bone Regency, South Sulawesi. Through a four-month internship and certified independent study program (MSIB), this activity involves identifying regional potential, counseling on rice cultivation and pest control. The research method uses quantitative data analysis with simple linear regression techniques and validity analysis using a Likert scale. The results of the study showed that the role of extension workers in providing socialization and guidance materials was very effective, with a validity level reaching 95.41%. Farmers also showed positive changes in their behavior towards controlling rat pests, with the same level of validity. This extension program succeeded in increasing farmers' knowledge and skills, and had a positive impact on agricultural productivity.